High-sensitivity pressure sensor using a polymer-embedded FBG - H., Ahmad; S. W., Harun; W. Y., Chong; M. Z., Zulkifli; M. M. M., Thant; Z., Yusof; Prabakaran, Poopalan (Wiley Periodicals, Inc., 2009)
Link to publisher's homepage at http://www3.interscience.wiley.com